THUNDERSTORMS, CHARGES AND CURRENTS - Ray, Baishali (European Scientific Journal, ESJ, 2015)
In the early part of the twentieth century, the diurnal variations of the fair weather electric field as a function of universal time (UTC) were characterized by the Carnegie and Maud research ships [e.g.,Whipple, 1929; Torreson et al., 1946]. The source of these variations in the global electric circuit (GEC) was theorized to trace directly to the diurnal variations in thunderstorms and electrified shower clouds [Wilson, 1921; Williams, 2009]. Much subsequent research on the global electric circuit has focused on linking the fair weather field variation, commonly called the Carnegie curve, to worldwide variations in electrified weather by using the proxy of thunderstorm or lightning statistics [e.g., Mach et al., 2011discussion]. What resulted from this research was long standing, unresolved scientific riddle: the diurnal variation global thunderstorm (and lightning) activity was in phase with but nearly twice the amplitude of the Carnegie Curve! A necessary and important step needed to address and solve this long standing discrepancy was providing actual observations of the electric current output and associated electrical generator strength of thunderstorms.